The Impact of Training and Career Development on Improving Gen-Z Employee Performance: A Study of Technology Startups: JEL Classification: M12, M53, M54, J24, O15 - Dyah Yusninda Agusty (Journal La Bisecoman, 2025)
The rapid growth of the technology startup industry in Jakarta is driving companies to strengthen human resource (HR) management, particularly in terms of training and career development programs for Generation Z employees. This study aims to evaluate the contribution of training and career development to improving the performance of Generation Z employees in the startup workplace in Jakarta. A descriptive qualitative method was used, utilizing a narrative questionnaire to explore respondents' experiences, perceptions, and assessments of the training programs they attended. Thirty respondents participated and provided descriptions of the relevance of the training materials, competency improvement, and its impact on daily work behavior. The results showed that the training provided by startups was deemed relevant and effective, particularly programs based on e-learning, mentoring, and project-based learning. 66.7% of respondents stated that the training methods were optimal. Career development was also well-evaluated, as evidenced by transparency in promotions, organizational support, and opportunities for further learning. Regarding performance, non-Gen Z employees' assessments indicated that Generation Z employees exhibit high levels of innovation (87.5%), collaboration (75%), and productivity (62.5%), although consistency and discipline still need to be strengthened. Overall, the results of this study confirm that training and career development support each other in improving the skills, enthusiasm, and performance of young employees, and serve as an important strategy for startups in creating a flexible and competitive digital workforce.